"Am I too emotional for this job?" An exploration of student midwives' experiences of coping with traumatic events in the labour ward. (February 2017) - Coldridge, Liz; Davies, Sarah
Abstract: Background: midwifery is emotionally challenging work, and learning to be a midwife brings its own particular challenges. For the student midwife, clinical placement in a hospital labour ward is especially demanding. In the context of organisational tensions and pressures the experience of supporting women through the unpredictable intensity of the labour process can be a significant source of stress for student midwives. Although increasing attention is now being paid to midwives' traumatic experiences and wellbeing few researchers have examined the traumatic experiences of student midwives. Such research is necessary to support the women in their care as well as to protect and retain future midwives. Aim: this paper develops themes from a research study by Davies and Coldridge (2015) which explored student midwives' sense of what was traumatic for them during their undergraduate midwifery education and how they were supported with such events. It examines the psychological tensions and anxieties that students face from a psychotherapeutic perspective. Design: a qualitative descriptive study using semi-structured interviews. Setting: a midwifery undergraduate programme in one university in the North West of England. Participants: 11 second and third year students. Analysis: interviews were analysed using interpretative phenomenological analysis. Findings: the study found five themes related to what the students found traumatic. The first theme Wearing the Blues referred to their enculturation within the profession and experiences within practice environments. A second theme No Man's Land explored students' role in the existential space between the woman and the qualified midwives. Three further themes described the experiences of engaging with emergency or unforeseen events in practice and how they coped with them ( "Get the Red Box!", The Aftermath and Learning to Cope) .This paper re-examines aspects of the themes from a psychotherapeutic perspective. Key conclusions: researchers have suggested that midwives' empathic relationships with women may leave them particularly vulnerable to secondary traumatic stress. For student midwives in the study the close relationships they formed with women, coupled with their diminished control as learners may have amplified their personal vulnerability. The profession as a whole is seen by them as struggling to help them to safely and creatively articulate the emotional freight of the role. Implications for practice: for midwifery educators, a focus on the psychological complexities in the midwifery role could assist in giving voice to and normalising the inevitable anxieties and difficulties inherent in the role. Further research could explore whether assisting students to have a psychological language with which to reflect upon this emotionally challenging work may promote safety, resilience and self-care. Highlights: Educators need to provide students with space to explore their anxieties in practice. Using containment models may help normalisation of students' anxieties. Facilitating containment was shaped by students' experiences of being contained. Students may need to learn psychological skills to protect themselves against trauma.